2016
DOI: 10.1016/j.bjid.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of coagulase-negative bloodstream isolates: detection of Staphylococcus epidermidis ST2, ST7 and linezolid-resistant ST23

Abstract: The mechanisms contributing to persistence of coagulase-negative staphylococci are diverse; to better understanding of their dynamics, the characterization of nosocomial isolates is needed. Our aim was to characterize phenotypic and molecular characteristics of Staphylococcus epidermidis and Staphylococcus haemolyticus human blood isolates from two tertiary care hospitals in Mexico, the Hospital Universitario in Monterrey and the Hospital Civil in Guadalajara. Antimicrobial susceptibility was determined. Biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
1
29
0
7
Order By: Relevance
“…The monitor for presence of FA resistance genes among S. epidermidis should be helpful for preventing the dissemination of fusidic acid resis- clone. ST23 was found among linezolid-resistant S. epidermidis isolates (32,33). In the present study, ST23 was identified in two S. epidermidis isolates with resistance to both mupirocin and FA.…”
Section: Discussionsupporting
confidence: 55%
“…The monitor for presence of FA resistance genes among S. epidermidis should be helpful for preventing the dissemination of fusidic acid resis- clone. ST23 was found among linezolid-resistant S. epidermidis isolates (32,33). In the present study, ST23 was identified in two S. epidermidis isolates with resistance to both mupirocin and FA.…”
Section: Discussionsupporting
confidence: 55%
“…However, the high frequency of the SCC mec IV in clinical isolates of S. epidermidis was already observed previously [4749], demonstrating that this SCC mec type has become a common occurrence among hospital isolates. In addition, it was observed in our study that the ccr2 complex that comprises the SCC mec type IV was also associated with BSI isolates.…”
Section: Discussionmentioning
confidence: 61%
“…Multidrug resistance is a significant concern in most health care settings worldwide because of the difficulties associated with clinical treatment and the potential of dissemination. It has been reported that the prevalent SE clonal lineages ST5, ST12, and ST23 often display high resistance toward most of the antibiotic classes (Martinez-Melendez et al 2016;Widerstrom et al 2012). Furthermore, there is evidence of increasing of rifampicin resistance over time in clinical SE isolates that belong to ST2 and ST23 from the USA, Australia, and some European countries (Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is evidence of increasing of rifampicin resistance over time in clinical SE isolates that belong to ST2 and ST23 from the USA, Australia, and some European countries (Lee et al 2018). Mutations in the rpoB gene conferring rifampicin resistance have emerged independently, suggesting the view that a limited number, well adapted multi-resistant clonal SE lineages, prevail in clinical settings (Lee et al 2018;Martinez-Melendez et al 2016). Reports of the profiles of antibiotic multi-resistance changes over time are scarce (Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%